2009
DOI: 10.1002/14651858.cd007209.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Enteral tube feeding for older people with advanced dementia

Abstract: Despite the very large number of patients receiving this intervention, there is insufficient evidence to suggest that enteral tube feeding is beneficial in patients with advanced dementia. Data are lacking on the adverse effects of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
232
0
42

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(276 citation statements)
references
References 37 publications
2
232
0
42
Order By: Relevance
“…Para pacientes com idade e demência avançada, a introdução e a continuidade da TNE por sonda ou gastrostomia, apesar de ser apropriada em alguns casos, priva o indivíduo da sensação de paladar, favorecendo a diminuição de sua dignidade e autoestima. Em geral, essa situação proporciona maior agitação, desconforto e necessidade de sedação nesses pacientes 5,18 .…”
Section: Terapia Nutricional Enteral Nos Cuidados Paliativos De Doençunclassified
“…Para pacientes com idade e demência avançada, a introdução e a continuidade da TNE por sonda ou gastrostomia, apesar de ser apropriada em alguns casos, priva o indivíduo da sensação de paladar, favorecendo a diminuição de sua dignidade e autoestima. Em geral, essa situação proporciona maior agitação, desconforto e necessidade de sedação nesses pacientes 5,18 .…”
Section: Terapia Nutricional Enteral Nos Cuidados Paliativos De Doençunclassified
“…For example, it is perfectly possible to compare the outcomes of artificial nutrition with not providing it, in terms of survival, pain, quality of life and so on (see Sampson et al [3] for a review). Although, note that either arm of this trial can be regarded as palliative care so, even if one arm does better, this doesn't tell us if palliative care is effective.…”
Section: Empiricalmentioning
confidence: 99%
“…There is no evidence that artificial feeding improves outcomes, and a recent Cochrane systematic review found insufficient evidence to suggest that enteral tube feeding is beneficial in patients with dementia. [51][52][53] Instead, dementia patients at the end of their lives benefit from a palliative approach, which would include hand-feeding for comfort if the patient indicates hunger. 54 …”
Section: Treating Nondementia Illnesses In Hospitalized Elders With Dmentioning
confidence: 99%